2004
DOI: 10.1074/jbc.m403891200
|View full text |Cite
|
Sign up to set email alerts
|

D1 Dopamine Receptor Mediates Dopamine-induced Cytotoxicity via the ERK Signal Cascade

Abstract: Postsynaptic striatal neurodegeneration occurs through unknown mechanisms, but it is linked to high extracellular levels of synaptic dopamine. Dopaminemediated cytotoxicity of striatal neurons occurs through two distinct pathways: autoxidation and the D1 dopamine receptor-linked signaling pathway. Here we investigated the mitogen-activated protein kinase (MAPK) signaling pathways activated upon the acute stimulation of D1 dopamine receptors. In SK-N-MC neuroblastoma cells, endogenously expressing D1 dopamine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 73 publications
4
76
1
2
Order By: Relevance
“…Thus, this further supports the hypothesis that the postsynaptic dopaminergic functions are altered in the absence of H3R. To study the mechanisms further, quinpirole and D1R agonist SKF-38393 were selected, as these compounds have previously been shown to activate ERK1/2 in cell cultures and striatal slices (Yan et al, 1999;Cai et al, 2000;Brami-Cherrier et al, 2002;Chen et al, 2004;Wang et al, 2005;Ferrada et al, 2009;Moreno et al, 2011). We found that both quinpirole and SKF-38393 induced ERK1/2 phosphorylation in wild-type, but not in H3R KO, mouse striatum.…”
Section: H3r Regulates Sensorimotor Gating and Dopaminergic Signalingsupporting
confidence: 75%
“…Thus, this further supports the hypothesis that the postsynaptic dopaminergic functions are altered in the absence of H3R. To study the mechanisms further, quinpirole and D1R agonist SKF-38393 were selected, as these compounds have previously been shown to activate ERK1/2 in cell cultures and striatal slices (Yan et al, 1999;Cai et al, 2000;Brami-Cherrier et al, 2002;Chen et al, 2004;Wang et al, 2005;Ferrada et al, 2009;Moreno et al, 2011). We found that both quinpirole and SKF-38393 induced ERK1/2 phosphorylation in wild-type, but not in H3R KO, mouse striatum.…”
Section: H3r Regulates Sensorimotor Gating and Dopaminergic Signalingsupporting
confidence: 75%
“…The activation of p38 MAPK and JNK has been reported to play a significant functional role in cell death induction (19). And curiously, ERK phosphorylation has been linked with both antitumor (29) and protumor (49) activities. Our results show that MCL induced the phosphorylation of p38 MAPK in both NPC tumor cells and also increased the activation of JNK from different time points.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from heterologous cell culture systems suggest that both D1-and D2-class dopamine receptors can regulate the MAP kinases extracellular-signal regulated kinases 1 and 2 (ERK1 and ERK2) (Beom et al, 2004;Chen et al, 2004b;Wang et al, 2005;Kim et al, 2006). In vivo, the administration of amphetamine (Beaulieu et al, 2006;Valjent et al, 2006b), cocaine (Berhow et al, 1996;Valjent et al, 2000), or the D2-class dopamine receptor antagonist haloperidol (Pozzi et al, 2003) has been shown to enhance striatal ERK1 and ERK2 phosphorylation.…”
Section: Coincidence Detection By Mitogen-activated Protein Kinasesmentioning
confidence: 99%